1996
DOI: 10.1039/cs9962500179
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of paper conservation

Abstract: There are probably more collectable objects based on paper than any other material: books, prints. drawings, watercolours, stamps. banknotes, matchbox labels etc. Not surprisingly, owners of such objects want them to remain in good condition despite the fact that many of them were only intended to have a lifetime of as little as a few hours. e.g. tickets. However, some papers and the images upon them are inherently unstable and others deteriorate quickly when stored under the wrong conditions.The study of pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 2 publications
1
42
0
Order By: Relevance
“…Ozone coming from electrical equipment is a likely source of such oxidation in libraries (Andretta et al 2016). Daniels (1996) showed that such effects can be accelerated by the presence of iron and copper in paper. Whitmore and Bogaard (1995) and Stephens et al (2009) showed that oxidation tends to make the paper more susceptible to mechanical breakdown during subsequent acid hydrolysis.…”
Section: Acidic Pollutants In the Airmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozone coming from electrical equipment is a likely source of such oxidation in libraries (Andretta et al 2016). Daniels (1996) showed that such effects can be accelerated by the presence of iron and copper in paper. Whitmore and Bogaard (1995) and Stephens et al (2009) showed that oxidation tends to make the paper more susceptible to mechanical breakdown during subsequent acid hydrolysis.…”
Section: Acidic Pollutants In the Airmentioning
confidence: 99%
“…It is well known that paper documents can be adversely affected by airborne oxidants such as ozone and nitrogen oxides (Arney et al 1979;Daniels 1996;Bogaard and Whitmore 2001;Stephens et al 2009). In fact, such oxidation appears to make the paper more susceptible to acid-catalyzed hydrolysis in some cases (Whitmore and Bogaard 1995;Stephens et al 2009).…”
Section: Other Conservation Treatments While Completing Deacidificatimentioning
confidence: 99%
See 1 more Smart Citation
“…The paper degrades naturally throughout three main reactions: acid-catalyzed hydrolysis of cellulose molecules, oxidative degradation induced from atmospheric oxygen and light, and thermal degradation that leads to chemical bond breakage as the temperature is increased. Artificial paper aging tests have demonstrated that these reactions become more intense when temperature is incremented [3]. Yellowing caused by aging, foxing that can appear due to iron oxidation or because of the presence of microorganisms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It is known (Daniels 1996) that paper degrades naturally through three main reactions: acid-catalysed hydrolysis of cellulose molecules, oxidative degradation induced from atmospheric oxygen and light, and thermal degradation that leads to chemical bond breakage as the temperature is increased. Artificial paper ageing tests have demonstrated that these reactions become more intense if temperature is incremented.…”
Section: (A) Paper Damage Under Ultraviolet Radiation and Femtosecondmentioning
confidence: 99%